Dahongpao mother tree affects soil microbial community and nutrient cycling by increasing rhizosphere soil characteristic metabolite content - Cheng, Weiting; Zhang, Shuqi; Wang, Yuhua; Hong, Lei; Qiu, Miaoen; Wang, Yulin; Luo, Yangxin; Zhang, Qi; Wang, Tingting; Jia, Xiaoli; Wang, Haibin; Ye, Jianghua (Frontiers in Plant Science, 2025)
Cuttings are an important way of propagating tea trees (Camellia sinensis). In this study, Dahongpao mother tree (MD) and cutting Dahongpao (PD) were used as research objects and their rhizosphere soil were collected and performed metabolomics analysis. At the same time, soil nutrient content, microbial physiological indexes, and microbial carbon source utilization were determined, which in turn obtained the effect of cuttings on metabolites, microorganisms, and nutrient cycling in rhizosphere soil of tea trees. The results showed that available nitrogen, available phosphorus and available potassium in the rhizosphere soil of MD were significantly higher (p < 0.05) than in PD. Secondly, microbial biomass carbon, microbial biomass nitrogen, microbial respiration, bacterial number, fungal number, and actinomycete number were also significantly higher in rhizosphere soil of MD than in PD. There were six groups of rhizosphere soil characteristic metabolites that differentiated MD from PD, of which the content of acid, amine, phenol, heterocyclic compound, alcohol and lipid was significantly higher in MD compared to PD, while carbohydrate content was significantly less in MD. There were five groups of rhizosphere soil microorganisms that differentiated MD from PD, in which microorganisms with carboxylic acid, amines, fatty acid and phenolic acid as carbon sources were significantly larger in MD than in PD, whereas microorganisms with carbohydrates as carbon sources were significantly smaller in MD than in PD. It can be seen that the number and content of rhizosphere soil characteristic metabolites were higher in MD than in PD. This enhanced the number of microorganisms with different carbon source utilization rates, increased microbial diversity and abundance, promoted nutrient transformation, increased the content of available nutrients, which in turn facilitated the growth of tea trees. This study provides an important reference for the use of metabolites to regulate soil microbial colonization, improve soil nutrient transformation, and maintain healthy growth of tea trees.